40th Annual Symposium on Foundations of Computer Science (Cat. No.99CB37039)
DOI: 10.1109/sffcs.1999.814576
|View full text |Cite
|
Sign up to set email alerts
|

A 5/2n/sup 2/-lower bound for the rank of n×n-matrix multiplication over arbitrary fields

Abstract: We prove a lower bound of ¾ Ò ¾ ¿Ò for the rank of Ò ¢Ò-matrix multiplication over an arbitrary field. Similar bounds hold for the rank of the multiplication in noncommutative division algebras and for the multiplication of upper triangular matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 12 publications
2
37
0
Order By: Relevance
“…The best known lower bounds for bilinear circuits for problems such as polynomial multiplication or matrix multiplication are given in Refs. [BD80,Blä99,Shp03,Kam05].…”
Section: Sketchmentioning
confidence: 99%
“…The best known lower bounds for bilinear circuits for problems such as polynomial multiplication or matrix multiplication are given in Refs. [BD80,Blä99,Shp03,Kam05].…”
Section: Sketchmentioning
confidence: 99%
“…Conversely, most lower bounds on matrix multiplication seem to have a border rank lower bound at their heart. For example, Landsberg (2008, Section 6) showed that the tensor rank lower bound of Bläser (1999)-the then best known bound-implicitly uses the same key lemma that Strassen (1983) used to give a border rank lower bound. The currently best known lower bound on tensor rank (Landsberg 2014b;Massarenti & Raviolo 2012) also uses techniques from the best known lower bound on border rank (Landsberg & Ottaviani 2011).…”
Section: Assumptionmentioning
confidence: 99%
“…We interpret various prior results in the language of tensor rank. For the matrix multiplication (which corresponds to a tensor of size [n 2 ] × [n 2 ] × [n 2 ]), Shpilka [Shp03] showed that the tensor rank is at least 3n 2 − o(n 2 ) over F 2 , and Bläser [Blä99] earlier showed that over any field the tensor rank is at least 2.5n 2 − Θ(n). For polynomial multiplication (which corresponds to a tensor of size [2n Kaminski [Kam05] showed that the tensor rank over F q is known to be (3 + 1/Θ(q 3 ))n − o(n) and earlier work by Brown and Dobkin [BD80] showed that over F 2 the tensor rank is at least 3.52n.…”
Section: Prior Workmentioning
confidence: 99%